Efficacy and safety assessment of propranolol tablets vs. oral solution for infantile hemangioma: a retrospective study in China - Chen, Wenting; Qian, Hua; Sun, Qi; Zhang, Shan; Zhu, Lei; Wu, Yafen; Qian, Yingying; Wang, Bingbing; Li, Wei (Frontiers in Pediatrics, 2025)
BackgroundPropranolol for infantile hemangiomas (IHs) is effective and relatively safe. However, propranolol has different formulations and there is no consensus on the optimal formulation for IHs. The propranolol oral solution was not used in China until 2022.ObjectiveTo evaluate the efficacy and safety of propranolol tablets and an oral solution in infants with high-risk IH.MethodsA retrospective cohort study was conducted involving 234 consecutive patients with a clinical diagnosis of high-risk IH who were treated with propranolol between August 2018 and February 2023 (propranolol tablets, 168 patients; propranolol oral solution, 66 patients). All patients were assessed in the hospital at the initiation of treatment and in the outpatient setting during treatment. The Hemangioma Activity and Severity Index was used to monitor the clinical activity of the hemangioma after propranolol treatment.ResultsBased on the Hemangioma Activity and Severity Index, 66.52% and 69.15% improvement occurred in the propranolol tablet and oral solution groups, respectively. 23.21% of patients in the propranolol tablet group and 42.42% in the oral solution group achieved >75% score improvement (X2 = 8.557; P = 0.003). Adverse reactions occurred in 34 (20.24%) and 11 patients (16.67%) in the propranolol tablet and oral solution groups, respectively. The most common adverse reaction in the propranolol tablet group was liver function abnormalities due to mild elevation of liver enzymes (X2 = 4.09; P = 0.045).ConclusionBoth propranolol tablets and oral solution had positive efficacy in patients with high-risk IHs, but more patients in the propranolol oral solution group achieve >75% score improvement compared to the propranolol tablet group. No life-threatening adverse reactions occurred in either group but liver function abnormalities were more likely to occur in patients treated with propranolol tablets.